β2-Glycoprotein I Deficiency and the Risk of Thrombosis - Bancsi, László F J M M; van der Linden, Irma K; Bertina, Rogier M (Thrombosis and Haemostasis, 1992)
β2-glycoprotein I (β2-GP I) is a plasma protein with a high affinity for negatively charged surfaces. In vitro this protein shows a variety of anticoagulant properties (inhibition of contact activation and platelet dependent prothrombinase activity). Therefore we studied the possibility that a hereditary β2-GP I deficiency is a risk factor for (familial) thrombophilia.Plasma β2-GP I levels were measured in healthy volunteers and four different groups of patients with (familial) thrombophilia. In these 5 groups the prevalence of β2-GP I deficiency (i. e. β2-GP I antigen <77%) was found to be very similar (6.8-12.5%) and statistically not significantly different. This observation suggests that β2-GP I deficiency in itself is not a risk factor for thrombosis.One thrombophilic patient was found to be homozygous deficient of β2-GP I. The transmission of the defect in his family followed autosomal inheritance. One of his brothers was also homozygous deficient and at the age of 35 years still free of thromboembolic complications.The possibility that β2-GP I deficiency could be an additional risk factor for the development of thrombophilia in families with protein C deficiency was evaluated in a panel of 70 unrelated patients with clinically dominant protein C deficiency. The prevalence of β2-GP I deficiency in this group of patients (12.8%) was very similar to that in other groups of normals and patients. Moreover, there was no difference in the frequency of β2-GP I deficiency in symptomatic and asymptomatic protein C deficient patients.